2016
DOI: 10.1038/ncomms11853
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial to mesenchymal transition is common in atherosclerotic lesions and is associated with plaque instability

Abstract: Endothelial to mesenchymal transition (EndMT) plays a major role during development, and also contributes to several adult cardiovascular diseases. Importantly, mesenchymal cells including fibroblasts are prominent in atherosclerosis, with key functions including regulation of: inflammation, matrix and collagen production, and plaque structural integrity. However, little is known about the origins of atherosclerosis-associated fibroblasts. Here we show using endothelial-specific lineage-tracking that EndMT-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
454
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(505 citation statements)
references
References 64 publications
(101 reference statements)
18
454
0
Order By: Relevance
“…In contrast, EndMT was associated with EC dysfunction and is implicated in pathological processes, including the induction of organ fibrosis 25 and atherosclerosis. 26,27 The full transition of ECs to mesenchymal or smooth muscle cells may promote vessel stability or maturation but would not allow the formation of perfused capillaries, as we demonstrate in the present study. Therefore, we speculate that a partial or reversible induction of EndMT may account for the formation of new capillaries after ischemia.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, EndMT was associated with EC dysfunction and is implicated in pathological processes, including the induction of organ fibrosis 25 and atherosclerosis. 26,27 The full transition of ECs to mesenchymal or smooth muscle cells may promote vessel stability or maturation but would not allow the formation of perfused capillaries, as we demonstrate in the present study. Therefore, we speculate that a partial or reversible induction of EndMT may account for the formation of new capillaries after ischemia.…”
Section: Discussionsupporting
confidence: 61%
“…Accumulating evidence supports that EndMT is a crucial contributor to endothelial injury [12, 22, 25]. We therefore evaluated the effects of LIPUS on EndMT by monitoring the changes of the specific endothelial markers (CD31 and VE-cadherin) and mesenchymal markers (α-SMA and FSP1) in HAECs.…”
Section: Resultsmentioning
confidence: 99%
“…EndMT is considered a part of the initial phase of coronary heart disease due to its promoting effects on the deposition and oxidation of lipoprotein, and on the inflammation and migration of endothelial cells [10, 11]. It is known that hydrogen peroxide (H 2 O 2 ) can induce EndMT [12], which may contribute to vascular diseases and endothelial cell dysfunction. In addition, accumulation of reactive oxygen species (ROS) can directly damage endothelial cells and indirectly modulate endothelial cell function via altering expression and function of the related genes [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been confirmed that EndMT is involved in CVDs such as PAH [22,23] and AS [3,4]. TGF-β1, a special multifunctional cytokine involved in the physiological and pathophysiological processes of the cardiovascular system, has been found to inhibit the vascular EC phenotype due to the disruption of endothelial intercellular junctions and the loss of apical-basolateral polarity [5,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that EndMT contributes to the development of vascular remodeling such as pulmonary arterial hypertension (PAH), atherosclerosis (AS), cardiac fibrosis and neointimal formation following vein graft transplantation into the arterial circulation [2]. In addition, human and animal studies have demonstrated a clear correlation between EndMT and the progression of AS [3], in which EndMT-derived fibroblasts were highly expressed in advanced atherosclerotic lesions [4]. Transforming growth factor β1 (TGF-β1) is a crucial cytokine for the initiation of EndMT as well as for vascular pathophysiology [5].…”
Section: Introductionmentioning
confidence: 99%